2022
DOI: 10.3390/cancers14153830
|View full text |Cite
|
Sign up to set email alerts
|

The Association between a Decrease in On-Treatment Neutrophil-to-Eosinophil Ratio (NER) at Week 6 after Ipilimumab Plus Nivolumab Initiation and Improved Clinical Outcomes in Metastatic Renal Cell Carcinoma

Abstract: A lower baseline neutrophil-to-eosinophil ratio (NER) has been associated with improved responses to immune checkpoint inhibitors (ICI)-treated metastatic renal cell carcinoma (mRCC). This study investigated the decrease in NER at week 6 after ipilimumab/nivolumab (ipi/nivo) initiation and treatment responses in mRCC. A retrospective study of ipi/nivo-treated mRCC at two US academic cancer centers was conducted. A landmark analysis at week 6 was performed to assess the association between the change in NER and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…Therefore, several studies have shown that an increase in eosinophil is a biomarker of irAEs occurences 17–20 . Although the detailed underlying mechanisms about association between eosinophils and irAEs occurrence are unclear, previous studies supported our data that increased eosinophils may reflect efficacy and safety in patients treated with ICIs 16,18,24–27,38 …”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Therefore, several studies have shown that an increase in eosinophil is a biomarker of irAEs occurences 17–20 . Although the detailed underlying mechanisms about association between eosinophils and irAEs occurrence are unclear, previous studies supported our data that increased eosinophils may reflect efficacy and safety in patients treated with ICIs 16,18,24–27,38 …”
Section: Discussionsupporting
confidence: 84%
“…[17][18][19][20] Although the detailed underlying mechanisms about association between eosinophils and irAEs occurrence are unclear, previous studies supported our data that increased eosinophils may reflect efficacy and safety in patients treated with ICIs. 16,18,[24][25][26][27]38 In the past, most studies have shown that ICImediated irAEs may be associated with an improved response to therapy and survival outcomes in several types of cancers. [43][44][45][46] Consistently, our data revealed significantly longer mOS and mPFS in patients with irAEs than in those without irAEs, as reported in another study (Figure 4A,B).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…KIRC patients with a high immune score were at increased risk, suggesting KIRC progressed when a significant proportion of immune cells were concentrated in the tumour microenvironment (TME). In recent years, immune checkpoint inhibitors have gradually become a mainstream therapy and research focus for KIRC ( 78 ) and are beneficial for improving the prognosis of patients ( 79 81 ). Relative to chemotherapy, treatment with immune checkpoint inhibitors does not appear to significantly increase risk of serious adverse events in COVID-19-positive patients ( 82 ).…”
Section: Discussionmentioning
confidence: 99%